Metastatic Breast Carcinoma to the Prostate Gland. (26th June 2016) - Kapp, Meghan E.; Giannico, Giovanna A.; Desouki, Mohamed Mokhtar
Abstract : Cancer of the male breast is an uncommon event with metastases to the breast occurring even less frequently. Prostate carcinoma has been reported as the most frequent primary to metastasize to the breast; however, the reverse has not been previously reported. Herein, we present, for the first time, a case of breast carcinoma metastasizing to the prostate gland. Prostate needle core biopsy revealed infiltrative nests of neoplastic epithelioid cells, demonstrated by immunohistochemistry (IHC) to be positive for GATA3 and ER and negative for PSA and P501S. A prostate cocktail by IHC study demonstrated lack of basal cells (p63 and CK903) and no expression of P501S. The patient's previous breast needle core biopsy showed strong ER positivity and negative staining for PR and HER2. Similar to the prostate, the breast was negative for CK5/6, p63, and p40. This case demonstrates the importance of considering a broad differential diagnosis and comparing histology and IHC to prior known malignancies in the setting of atypical presentation or rare tumors.